Closed versus conventional IV catheter in performing coronary CT Angiography - Mohamed M. Harraz; Ahmed H. Abouissa; Wael H. Kamr (The Egyptian Journal of Radiology and Nuclear Medicine, 2020)
Abstract Background The purpose of this study was to compare the performance of a closed IV catheter system (CICS) with conventional IV catheters for IV contrast infusion in terms of contrast enhancement and associated complications during coronary CT angiography. It is a retrospective study of 54 patients for whom a follow-up CCTA was requested were included for this study. Those patients had previous experience with the insertion of a 18 g conventional IV catheter which allows a flow rate of ≥ 6 ml/s and the complications during injection were registered. Patients were informed that a new IV catheter (The BD Nexiva™ Diffusics™ Closed IV Catheter System 22 g while still meeting a high flow rate > 6 m/s) will be used for their examination. We analyzed mean vascular attenuations in the ascending aorta, left main coronary artery, left ventricular (LV) cavity, and descending aorta (DA). Their feedback was collected regarding pain and the number of trials for catheter insertion. In addition, the access site was evaluated for any complication e.g. perforation, contrast extravasation or contamination. Result All patients were very satisfied with the new cannula. The catheter was inserted from the first trials. No one has perforation or extravasation. Mean vascular attenuations of the left main coronary artery, LV cavity, and DA were significantly higher during the use 0f the BD Nexiva™ Diffusics™ Closed IV Catheter System (all P ≤ 0.001). Conclusion Although the CICS has a small lumen, it allows a high flow rate; therefore, IV access required for CCTA can be secured with higher vascular attenuation and fewer complications. It is encouraged to use the CIVC system for CT angiographic studies, in particular CCTA.